The optimal placement and sizing of distributed generation in an active distribution network with several soft open points - Karunarathne E.; Pasupuleti J.; Ekanayake J.; Almeida D. (MDPI AG, 2023)
Computer science; Energy management; Active distribution network (ADN); Active distribution networks; Active power loss; Distributed generator (DGs); Network condition; Network structures; Optimal placement and sizings; Optimization framework; Distributed power generation